Digital Media-based Quantum Learning: Improving Students’ German Writing, Critical Thinking and Learning Motivation - Akihary, Wilma; Apituley , Patresia S. (REiLA : Journal of Research and Innovation in Language, 2022)
The quantum learning model is a combination of various interactions that occur during the learning process. This learning model can be combined with the Assoziogram technique or also with audio-visual media as learning media. This research aims at investigating the implementation of a digital media-based quantum learning model with the Assoziogramm technique/concept map to improve students’ German writing, critical thinking, and learning motivation. This research uses one group pre-test and post-test experimental research design with a total sample of 20 students. The research data were collected using test and non-test (questionnaire) instruments. The research data were analysed using descriptive statistics and paired t-tests. The study results show an increase in the ability to write German, critical thinking, and learning motivation after the implementation of the digital media-based quantum learning model with the Assoziogramm technique. This study contributed to showing how variations in learning are crucial in providing a more engaging learning climate than the conventional learning done by lecturers.